Secondary aerosol formation during the dark oxidation of residential biomass burning emissions. Issue 5 (31st August 2022) - Kodros, John K.; Kaltsonoudis, Christos; Paglione, Marco; Florou, Kalliopi; Jorga, Spiro; Vasilakopoulou, Christina; Cirtog, Manuela; Cazaunau, Mathieu; Picquet-Varrault, Bénédicte; Nenes, Athanasios; Pandis, Spyros N.
Abstract : Biomass burning emissions age rapidly in the dark due to oxidation reactions with nitrate radicals. Abstract : Particulate matter from biomass burning emissions affects air quality, ecosystems and climate; however, quantifying these effects requires that the connection between primary emissions and secondary aerosol production is firmly established. We performed atmospheric simulation chamber experiments on the chemical oxidation of residential biomass burning emissions under dark conditions. Biomass burning organic aerosol was found to age under dark conditions, with its oxygen-to-carbon ratio increasing by 7–34% and producing 1–38 μg m −3 of secondary organic aerosol (5–80% increase over the fresh organic aerosol) after 30 min of exposure to NO3 radicals in the chamber (corresponding to 1–3 h of exposure to typical nighttime NO3 radical concentrations in an urban environment). The average mass concentration of SOA formed under dark-oxidation conditions was comparable to the mass concentration formed after 3 h (equivalent to 7–10 h of ambient exposure) under ultraviolet lights (6 μg m −3 or a 47% increase over the emitted organic aerosol concentration). The dark-aging experiments showed a substantial increase in secondary nitrate aerosol (0.12–3.8 μg m −3 ), 46–100% of which is in the form of organic nitrates. The biomass burning aerosol pH remained practically constant at 2.8 throughout the experiment. This value promotes inorganic nitrate partitioning to the particulate phase, potentially contributing to the buildup of nitrate aerosol in the boundary layer and enhancing long-range transport. These results suggest that oxidation through reactions with the NO3 radical is an additional secondary aerosol formation pathway in biomass burning emission plumes that should be accounted for in atmospheric chemical-transport models.